Geology of Pletovarje motorway tunnel (Slovenia) - Magda Čarman; Borut Petkovšek; Tomaž Budkovič (Geologija, 2009)
Styrian motorway crosses the Pletovarje ridge through the tunnel having the same name. It intersects the mosteastern extension of the Southern Karavanke tectonic unit. Considering geological conditions, the tunnel couldbe divided into three sections: the inner Donat / Dona~ka fault zone composed of tectonic lenses of differentlithostratigraphic units (of paleozoic, triassic and tertiary age), massive dolomite (lower triassic) and Smrekovecseries of oligocene age. Main faults have east – west direction and are subvertical.